Wanprestasi pada Perjanjian Jasa Joki (Pemain Bayaran) pada Game Mobile Legends: Suatu Penelitian di Kota Padangsidimpuan - Candra Yusuf Siregar; Mustakim Mustakim (CV. Rumoh Aceh Publishing, 2026)
Pasal 1320 KUHPerdata, one of the conditions for a valid agreement is the existence of an agreement between both parties. In practice, what often happens in the field is that one party commits a breach of contract by ignoring the previously agreed terms. The purpose of this study is to explain the forms of breach of contract that occur in Mobile Legends game boosting service agreements, the factors that cause the breach of contract, and the efforts to resolve breaches that occur between consumers and Mobile Legends game boosting service providers. Data collection was conducted through field research and library research. Field research was carried out by interviewing respondents and informants, while library research was conducted by studying legislation, textbooks, and scholars' opinions relevant to the issues being investigated. Based on the research results, it was found that the service agreement for hiring Mobile Legends online game boosters has been determined and agreed upon by both parties at the beginning of the agreement. The types of breaches that occur in mobile legends game boosting service agreements are performing partially, performing what was promised but late, and doing things prohibited in the agreement. The factors causing breaches in mobile legends game boosting service agreements are the limited abilities of the booster service provider and limited time. Resolution of breaches in mobile legends game boosting service agreements is done non-litigation, namely through negotiation. The recommendation from this study is that users of Mobile Legends game boosting services should be more cautious with personal data and account misuse when using game boosting services. Before making a transaction, it is advisable to ensure that your account is safe and cannot be hacked, which can be done by linking the account to several other platform accounts, such as Moonton, Facebook, Google Play, to ensure the security of your account, and to be wiser in choosing services that are already safely affiliated and not easily tempted by promotions and low prices.